2020
DOI: 10.1186/s13075-020-02224-w
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal blood pressure dipping as a marker of endothelial function and subclinical atherosclerosis in pediatric-onset systemic lupus erythematosus

Abstract: Background: Loss of the normal nocturnal decline in blood pressure (BP), known as non-dipping, is a potential measure of cardiovascular risk identified by ambulatory blood pressure monitoring (ABPM). We sought to determine whether non-dipping is a useful marker of abnormal vascular function and subclinical atherosclerosis in pediatriconset systemic lupus erythematosus (pSLE). Methods: Twenty subjects 9-19 years of age with pSLE underwent ABPM, peripheral endothelial function testing, carotid-femoral pulse wave… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 51 publications
3
25
0
1
Order By: Relevance
“…Therefore, findings from the current study may provide evidence on the mechanism linking air pollution to increased CVD risk, and potential preventive measurements, such as a well-controlled BP and taking ARBs, to attenuate the adverse impacts of PM 2.5 . Sympathetic nerve activation may play a role in the morning BP surge (8), and nocturnal BP non-dipping may be associated with endothelial dysfunction (9). In accordance with the findings of this study, people reaching well-controlled BP had more stable ANS, hence the adverse impacts of PM 2.5 on morning BP surges were attenuated.…”
Section: Discussionsupporting
confidence: 87%
“…Therefore, findings from the current study may provide evidence on the mechanism linking air pollution to increased CVD risk, and potential preventive measurements, such as a well-controlled BP and taking ARBs, to attenuate the adverse impacts of PM 2.5 . Sympathetic nerve activation may play a role in the morning BP surge (8), and nocturnal BP non-dipping may be associated with endothelial dysfunction (9). In accordance with the findings of this study, people reaching well-controlled BP had more stable ANS, hence the adverse impacts of PM 2.5 on morning BP surges were attenuated.…”
Section: Discussionsupporting
confidence: 87%
“…Additionally, in a study of adolescents with type 1 diabetes, non-dipping at baseline was associated with microalbuminuria at follow up 25 . In a cross-sectional analysis of a hypertensive pediatric cohort, proteinuria was significantly associated with non-dipping 26 .With regards to cardiovascular outcomes, analyses of pediatric cohorts have reported significant associations between BP non-dipping and pulse wave velocity, carotid-intima medial thickness, and coronary artery calcium presence [27][28][29] .…”
Section: Discussionmentioning
confidence: 99%
“…In turn, De la Sierra et al [ 29 ] emphasize that the highest cardiovascular risk is found in people with an abnormal non-dipper profile and the presence of nocturnal hypertension. Chang et al [ 13 ] in the paediatric-onset SLE population found an early development of subclinical atherosclerotic lesions in the form of increased IMT and PWV acceleration, which were particularly correlated with abnormal nocturnal systolic blood pressure dipping and non-dipper profile. These results are consistent with the observations obtained from our studies confirming the association of higher IMT with the presence of an abnormal nocturnal blood pressure profile and the presence of additional atherosclerotic plaques in the carotid arteries.…”
Section: Discussionmentioning
confidence: 99%
“…People with an insufficient decrease in blood pressure (BP) at night compared to the hours of daily activity (non-dipper) have a significantly higher cardiovascular risk, also in the case of correct BP values in office measurements [9][10][11]. It seems that the association with early, as well as subclinical, atherosclerotic changes in vessels, not only of the coronary circulation, such as increased intima media thickness (IMT), presence of atherosclerotic plaques in carotid arteries, or increased stiffness of their walls, may be associated with the presence of nocturnal hypertension, including its particular form of isolated nocturnal hypertension [12][13][14][15]. There are many processes and mechanisms underlying the dysregulation of the blood pressure profile.…”
Section: Introductionmentioning
confidence: 99%